CYTOTOXIC AND ANTIMICROBIAL STUDIES OF SOME SUBSTITUTED PYRAZOLINE DERIVATIVES DERIVED FROM ACETYL HYDRAZINES - BHAT K, ISHWAR; PJ, JAINEY (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objectives: Several pyrazoline derivatives have been developed as chemotherapeutic agents and have found wide clinical applications such as anticancer [4], antibacterial [4], antifungal [4], antitubercular [4] agents. Chalcones with an enone system between two aromatic rings exhibit interesting pharmacological activities such as anti-inflammatory, antileishmanial, antibacterial, antifungal, antitumour, antimalarial and anti-tubercular activity. To synthesize series of pyrazolines from chalcones and to evaluate the antimicrobial activities of the synthesized compounds. Methods: Chalcones were synthesized from various substituted aldehydes condensing with various substituted acetophenones and cyclized into Pyrazolines using aryloxy acetyl hydrazines. Antimicrobial and Antitubercular activity studies were carried out. Results: Antimicrobial studies for the synthesized Pyrazolines revealed that some compounds have showed promising activity. Conclusions: The above results proved that Pyrazolines are found to be interesting lead molecules for further synthesis as Antimicrobial and Antitubercular agents. Keywords: Chalcones, Pyrazolines, Antimicrobial Activity, Â Antitubercular Activity.